Towards a sustainable future of the Indigenous youth : Arctic negotiations on (im)mobility - Toivanen, Reetta (2021)
Based on ethnographic research in the northernmost part of Finland, Norway and Russia (Barents region), this chapter analyses the elements of wellbeing and discusses the (im)mobility dilemma of Indigenous youth in the Arctic. Wellbeing is here understood as lived citizenship that encompasses the feeling of being in charge of one’s own life path. The dilemma of (im)mobility presupposes that young people need to decide between staying in (traditional or new) professions in the Arctic area or leave for the cities. This dilemma is supported by dominant contradictory narratives surrounding the Arctic and its inhabitants, which leave little space for the local people. The chapter asks whether there is necessarily an either/or demand, to stay or to leave, for the Indigenous youth. The young Indigenous peoples living in the Arctic challenge these discourses in multifarious ways. They do not, as assumed in much of the literature on minorities and language and culture loss, necessarily abandon their cultures, languages and lands in the case that they physically move away. Using the example of Sámi youth in Finland, this chapter argues that young Indigenous people are finding creative ways to challenge the dominant societal discourses that have for decades deprived them of agency. Peer reviewed